Az Alföld földhasznosítási szerkezetének várható átalakulása - Berényi, István (Tér és Társadalom, 1993)
Hungarian agriculture had a successful period between 1965–1985 from the point of view of mere production, the foundation of which were the lucky combination of the big farms and private enterprises (homesteads), and also the mass production background which was provided by the COMECON-market. The crisis signs of the agrarian production built on the complicated system of state subsidies appeared in the beginning of the 1980s. By that time the machinery of the big farms had lost its value. At the same time the prices of the industrial products necessary for the maintenance of the levei of production (fertiliser, pesticides, machines etc.) had gone up. The market became narrower, because the importing socialist countries lost their solvency one after the other. In 1985, 40% of the big farms were not able to prodiice the criteria of the reproduction. After the change of 1989 he European market widened theoretically, but not to the extent that could mean a way out of the over-production crisis. In fact, the appearance of Hungarian and Eastem European agrarian products on the Western European market brought focus on the inner contradictions of the EC agrarian policy. According to Henrichsmeyer, an eventual agrarian reform of the EC would result in a 30-40% decline in the collection prices, another 15% decrease in the agricultural land and the growth of the extensive features of production. There is a very slight chance that the Community can take all these up in these years. Thus the crisis Hungarian agriculture were brought about by the continuous and unfavourable changes of inner and outer conditions. A quick change of paradigm cannot be expected, since the new European frameworks in which the obviously overgrown home agrarian production has to find its place rare still unknown. The gradual formation of the common European market forces the reconstruction of the structure of agricultural production, and also the reformation of land use structure. From the point of view of the change of the land use structure, it is evident that those parts of the country will be intensively or less intensively tilled that have certain comparative advantages (fertility, transportation-market location, social-settlement background etc.) in the home or European regional system. In our study we defined the region of the Great Plain with different productive potentials that, in our opinion, have special agrarian potentials from the aspects of regional planning and settlement development, and the ownership and productive relations, the whole vertical system of production has to be transformed according to this. This has to be based mainly on the local natural-economic-social resources, and the whole of the stimulation should be built on it. According to the above-mentioned requirements we defined the following spatial types: I. The natural endowments and the economic-social background of the production forces the maintenance of the agrarian structure, the opportunity for change is little and slow. II. Though the natural conditions of the production are favourable, some elements of the present economic-social background fend difficulty in adjusting themselves to the new-type agrarian production, thus the directions of the production must be found. III. In these type areas the crisis of the agrarian production is the consequence of the big farm system, amounting to monoculture, strengthening and conserving the agrarian features of the social structure and resulting in the functional decline in the importance of the agrarian towns. In these areas the decrease of the production in inevitable, also the reformation of the structure and the construction of the vertical system of production, procession and marketing. IV. The Great Plain has got special agrarian regions, e.g. areas of intensive wine and fruit production, or, on the other hand, areas with extremely extensive culture (Hortobágy), that require special regional developmental conception. This brief summery of the regional types is meant to support the view that the development of the Great Plain cannot be considered as a homogeneous region from the point of view of agrarian production, so a regionally "sensitive" developmental conception has to bé worked out, which is a part of a long term regional developmental notion.